Effect of Unsaturated Flow Modes on Partitioning Dynamics of Gravity‐Driven Flow at a Simple Fracture Intersection: Laboratory Study and Three‐Dimensional Smoothed Particle Hydrodynamics Simulations. Issue 11 (22nd November 2017) - Kordilla, Jannes; Noffz, Torsten; Dentz, Marco; Geyer, Tobias; Tartakovsky, Alexandre M.
Abstract: In this work, we study gravity‐driven flow of water in the presence of air on a synthetic surface intersected by a horizontal fracture and investigate the importance of droplet and rivulet flow modes on the partitioning behavior at the fracture intersection. We present laboratory experiments, three‐dimensional smoothed particle hydrodynamics (SPH) simulations using a heavily parallelized code, and a theoretical analysis. The flow‐rate‐dependent mode switching from droplets to rivulets is observed in experiments and reproduced by the SPH model, and the transition ranges agree in SPH simulations and laboratory experiments. We show that flow modes heavily influence the "bypass" behavior of water flowing along a fracture junction. Flows favoring the formation of droplets exhibit a much stronger bypass capacity compared to rivulet flows, where nearly the whole fluid mass is initially stored within the horizontal fracture. The effect of fluid buffering within the horizontal fracture is presented in terms of dimensionless fracture inflow so that characteristic scaling regimes can be recovered. For both cases (rivulets and droplets), the flow within the horizontal fracture transitions into a Washburn regime until a critical threshold is reached and the bypass efficiency increases. For rivulet flows, the initial filling of the horizontal fracture is described by classical plug flow. Meanwhile, for droplet flows, a size‐dependent partitioning behavior is observed, and the filling of the fracture takes longer. For the case of rivulet flow, we provide an analytical solution that demonstrates the existence of classical Washburn flow within the horizontal fracture. Key Points: Partitioning dynamics at wide aperture fracture intersections depend on unsaturated flow modes Onset of characteristic Washburn regime from nonequilibrium conditions until steady state is determined Smoothed particle hydrodynamics can reproduce complex free surface flows dominated by surface tension